2000
DOI: 10.2754/avb200069010033
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Gestagen, Serum and Milk Progesterone Concentrations in Ewes of the Jezersko-Solchava Breed

Abstract: The aim of the study was to obtain information about the characteristics of the serum progesterone, faecal gestagen and milk progesterone patterns in the ewes during oestrous cycle, pregnancy and postpartum period. The study was performed in seven adult ewes of the JezerskoSolchava breed. The faecal gestagens were extracted by methanol and hormone concentrations determined by EIA. During the oestrous cycle, lasting 16 days in average, low serum progesterone and faecal gestagen values were found in the follicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
2
3
1
Order By: Relevance
“…This value was similar to that reported by Cebulj-Kadunc et al (2000) in sheep (11.4%). It was slightly higher than that published by Isobe et al (2005) in bovine, which was about 10.9%.…”
Section: Results and Discussion Analytical Validationsupporting
confidence: 81%
See 2 more Smart Citations
“…This value was similar to that reported by Cebulj-Kadunc et al (2000) in sheep (11.4%). It was slightly higher than that published by Isobe et al (2005) in bovine, which was about 10.9%.…”
Section: Results and Discussion Analytical Validationsupporting
confidence: 81%
“…This coefficient was similar to that found by Dantzer et al (2010) for cortisol (17.9%). However, this coefficient was higher than that obtained by Korndö rfer et al (1998) in rabbit (15.7%) and Cebulj-Kadunc et al (2000) in sheep (13.8%) for progesterone. The intra and inter-assay coefficient variation for a sample having high concentration plasmatic of P4 were, respectively, equal to 17.3% and 17.6%.…”
Section: Results and Discussion Analytical Validationcontrasting
confidence: 51%
See 1 more Smart Citation
“…The blood hormone profile during pregnancy in ewes has been previously described (21)(22)(23) , and the serum progesterone and estrone levels during pregnancy obtained in this study corroborated previous reports. The high correlation between serum progesterone levels and fecal metabolites during pregnancy was also observed by Cebulj-Kadunc et al (14) in ewes. Additionally, Borjesson et al (5) also demonstrated a high correlation between serum and fecal progesterone levels in wild ewes.…”
Section: Discussionsupporting
confidence: 77%
“…Considering the metabolism and excretion pathways of reproductive steroid metabolites (12) , some researchers have evaluated the use of fecal samples for hormone monitoring in sheep. Fecal metabolites of progesterone were evaluated during the estrous cycle and pregnancy in domestic (Ovis aries) (13,14) and wild (Ovis canadensis) (5) ewes, observing a high correlation between fecal metabolites and serum progesterone levels. Additionally, Schoenecker et al (6) also evaluated progesterone and estrone fecal metabolite levels in pregnant ewes, but the hormone levels were not correlated with the serum levels.…”
Section: Introductionmentioning
confidence: 99%